Source to Sink study at continent-scale: Africa since 145 Ma - (:unkn) unknown (My University, 2019)
A source to sink study was performed at the scale of Africa based on (1) the measurement of the compactedsiliciclastic sediment volumes preserved in the African Basins (margins, rifts, intracratonic), for the sink (see forthe method in Guillocheau et al., 2012, Basin Research) and (2) the measurement of the eroded volumes obtainedby the difference of elevation between the modern topography and remarkable deformed planation surfaces(etchplains or pediplains), for the source (see for the method in Guillocheau et al., 2018, Gondwana Research).Two main planation surfaces of Upper Cretaceous and Middle Eocene age were mapped. They are weatheringsurfaces (etchplains) known as the African Surface(s).(1) The sink analysis shows evidences of three periods of major denudation of Africa during Early Cretaceous(145-125 Ma, Berriasian-Barremian), Late Cretaceous (94-80 Ma) and uppermost Eocene to today (40-0 Ma).They record major Africa-scale uplifts related to mantle dynamics. The Cenozoic is a period of increase of thesiliciclastic sediment volumes with a paroxysm during Plio-Pleistocene (5.5-0 Ma), here related to the dynamic ofthe Southern African superplume and not to climate changes.(2) The range of the sedimentation rates is between 5 and 80 x 103 km3/Ma, i.e. the rates of passive margin out ofdirect feeding by active mountain belts.(2) The analysis of the denudation through time shows two different spatial patterns: from 94 to 80 Ma, denudationis located all over Africa and from 40 to 0 Ma, only along the “coastal” plain of Africa (with the noticeableexception of the Congo catchment). This is interpreted as different modes of plate deformation and relief growth.(3) The source to sink budgets has been performed on the catchment of the Congo, Orange, Zambezi and EastAfrican rivers from 94-80 Ma to today. Surprisingly, they show equilibrated balances, suggesting low chemicalerosion and/or neoformation of sedimentary particles (mainly clays: kaolinites to s
Keywords: African Research